A highly specific probe for the imaging of inflammation-induced endogenous nitric oxide produced during the stroke process. Issue 18 (27th August 2020) - Li, Chenchen; Hu, Wei; Wang, Jinchen; Song, Xinjian; Xiong, Xiaoxing; Liu, Zhihong
Abstract : A two-photon fluorescent probe with high selectivity and sensitivity was constructed and applied to image stroke-induced NO inflammation. Abstract : In this study, a turn-on two-photon fluorescent probe (Lyso-TP-NO ) for nitric oxide (NO) was developed. It was synthesized using 4-ethylamino-1, 8-naphthalimide as the two-photon fluorophore and N -methylaniline moiety as the reaction site. The probe and fluorophore were tested under one- and two-photon modes. The fluorescence intensity of the system was enhanced 23.1-fold after reacting with NO in the one-photon mode. However, the maximal two-photon action cross-section value of 200 GM was obtained under excitation at 840 nm. The probe exhibits high selectivity and sensitivity over other reactive oxygen species (ROS) and reactive nitrogen species (RNS), with a detection limit as low as 3.3 nM. The two-photon fluorescence imaging of living cells and mouse brain tissues can capture inflammation-induced endogenous NO production in lysosomes during stroke occurrence.